RESONANCE AND FREQUENCY CHARACTERISTICS OF VOWELS: A COMPARATIVE ACOUSTIC STUDY OF SUNDANESE AND NON-SUNDANESE SPEAKERS - Nur'hasanah, Ilma Aprianti; Ramadhan, Hilman Nuha; Amalia, Yiyin Ema; Koharu, Koharu; Suwandi, Galih Restu Fardian (JOURNAL ONLINE OF PHYSICS, 2026)
This study aims to analyze the fundamental frequency and formant values of speech to identify differences in acoustic characteristics between Sundanese and non-Sundanese ethnic groups. The analysis was conducted by measuring the fundamental frequency and formant values of vowel sounds produced by both groups. Speech data were recorded using acoustic software and analyzed using both descriptive and inferential methods. Descriptive statistics, including mean analysis, were used to illustrate the data's general characteristics. In contrast, inferential statistics were performed using t-tests in SPSS to compare formant and fundamental frequency values between the two groups. The findings reveal no significant differences in vowel acoustic characteristics between Sundanese and non-Sundanese speakers, particularly in formant distribution patterns. This research contributes to understanding the relationship between linguistics and bioacoustics and opens up further applications in phonetics and speech analysis. Specifically, for the F1 results, the vowel /u/ showed a lower frequency than /e/ and /eu/ due to a more closed mouth opening pattern. In F2, /u/ also exhibited lower values because of a deeper tongue position and more closed articulation. In F3 and F4, the vowel /e/ had the lowest values, attributed to a smaller oral cavity and lower tongue pressure, which affect airflow. Based on statistical tests, no significant differences were found in the vowel samples /e/, /eu/, and /u/ between Sundanese and non-Sundanese speakers, as indicated by t-test values greater than 0.05.